Comparative Evaluation of fluoride releasing and recharging ability for various pit and fissure sealants (An in vitro study). - Vian O. Majeed (Erbil Dental Journal)
Background and Objective: This study was conducted to evaluate the releasing and recharging ability of fluoride for four different types of pit and fissure sealants. Methods: Four different pit and fissure sealants: GIC Ketac® Cem radiopaque, 3M ESPE, Photac Fill, 3M ESPE (light-curing, GIC), Palfique (Universal flow, Tokuyama) and Charisma (composite) were used in this study, ten cylindrical specimens were prepared of each material (10 mm in diameter and 1 mm in thickness). Specimens were dipped in 5 ml deionized water and fluoride release was detected using a fluoride-specific ion electrode every day from 1,2,3,4,5,6,7,14,21 and 28 days. On day 28, specimens were exposed to a fluoride varnish and then dipped in water, and then the fluoride concentration was measured after 24 hours and one week. Results: All sealants revealed the highest fluoride release on the first day after dipping and the fluoride release sharply decreased after 24 hs and slowly decreased after 3 days. On the first day, Ketac presented the highest fluoride release (37.8 µg/cm2 ±0.12) followed by Photac (36.4 µg/cm2 ±0.45), Palfique (15.5 µg/cm2 ±1.16) and Charisma (8.2 µg/cm2±0.026). Both Ketac and Photac were statistically significant with Palfique and Charisma in all experimental fluoride release periods. After fluoride uptake, Ketac and Photac released the highest fluoride (7.8 µg/cm2±0.52, 7.3 µg/cm2±0.53) respectively after 24 hours followed by Palfique (2.4 µg/cm2±0.11) and Charisma showed the lowest fluoride release(0.37 µg/cm2±0.025). Conclusions: Within the limitations of this short term study, two glass ionomers were shown to have highest capacity in fluoride release and uptake, followed by Palfique and fluoride releasing composite.